ARTISTIC AND COMPOSITIONAL REGULARITIES OF CALENDAR SYSTEMS DESIGN IN HERITAGE OBJECTS OF CULTURE AND ART OF ANCIENT CIVILIZATIONS - Гамалія, К. М.; Гальчук, Я. Є. (Art and Design, 2021)
The purpose of the article is to study and create general comparative analysis of the formation and compositional techniques of complex calendar structures in the culture of Ancient Egypt, Ancient Greece and Ancient Rome, to study the connection and interaction between their sign systems. Methodology. The study of the principles of the representation of ancient calendar systems is based on historical-cultural, comparative, hypothetical-deductive and logical methods. Analytical method allowed to compare font compositions and artistic, figurative, formal and formal integrity of calendars. The results of the study, the features, differences and patterns of interpretation and design of the calendar structures of the periods of Ancient Egypt and Antiquity were analyzed and compared. The scientific novelty of the research lies in the fact that for the first time a clear characteristic of the representation of calendar structures in the objects of the cultural heritage of Ancient Egypt, Ancient Greece and Ancient Rome was analyzed and revealed:- the visual sign system and the principles of its informative content were compared;- identified methods of design in relation to scale, compositional techniques, graphics, techniques and representation technology are determined;- the cause-and-effect consistent patterns of the processes of artistic formation have been clarified. Practical significance. The application of the research results allows to diversify and enrich the courses of disciplines in the general history of art and culturology, archeography, source studies, et cetera. The features of the composition and calligraphy of calendar systems specified in the article can be applied in the field of graphic design, and serve in semiological and art historian researches.